2010
DOI: 10.1128/jb.00058-10
|View full text |Cite
|
Sign up to set email alerts
|

Copper Stress Affects Iron Homeostasis by Destabilizing Iron-Sulfur Cluster Formation in Bacillus subtilis

Abstract: Copper and iron are essential elements for cellular growth. Although bacteria have to overcome limitations of these metals by affine and selective uptake, excessive amounts of both metals are toxic for the cells. Here we investigated the influences of copper stress on iron homeostasis in Bacillus subtilis, and we present evidence that copper excess leads to imbalances of intracellular iron metabolism by disturbing assembly of iron-sulfur cofactors. Connections between copper and iron homeostasis were initially… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

16
178
0
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 197 publications
(201 citation statements)
references
References 63 publications
16
178
0
2
Order By: Relevance
“…The ability to store and protect Cu I ions in the cytosol is driven by the formation of thiolate‐coordinated tetranuclear clusters in both prokaryotes and eukaryotes, but is achieved with dramatically different protein structures. Paradoxically, the same facile cluster chemistry of Cu I is also responsible for toxicity by the displacement of iron at Cys‐bound 4Fe–4S clusters 27, 28, 29, 30. MTs have been suggested to contribute to a “chelation” rather than “compartmentalization” mechanism to combat copper toxicity in eukaryotes 27.…”
mentioning
confidence: 99%
“…The ability to store and protect Cu I ions in the cytosol is driven by the formation of thiolate‐coordinated tetranuclear clusters in both prokaryotes and eukaryotes, but is achieved with dramatically different protein structures. Paradoxically, the same facile cluster chemistry of Cu I is also responsible for toxicity by the displacement of iron at Cys‐bound 4Fe–4S clusters 27, 28, 29, 30. MTs have been suggested to contribute to a “chelation” rather than “compartmentalization” mechanism to combat copper toxicity in eukaryotes 27.…”
mentioning
confidence: 99%
“…When in excess, however, copper is highly toxic to living cells, as it interacts with free proteinogenic thiol groups, destabilizes iron-sulfur cofactors, competes with other metals for protein binding sites, and possibly leads to formation of reactive oxygen species (Chillappagari et al, 2010;Hiniker et al, 2005;Macomber & Imlay, 2009). Remarkably, disturbance of copper homeostasis is thought to lead to human diseases such as Alzheimer's disease, Parkinson's disease, Wilson's disease and Menkes syndrome (Barnham & Bush, 2008;Lenartowicz et al, 2011;Lutsenko, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Increased intracellular Cu(I) ions destabilize ironsulfur clusters, leading to functionally inactive proteins. Genome-wide transcriptome analysis of Bacillus subtilis has demonstrated that numerous genes for iron-sulfur cluster-containing enzymes, including those involved in the electron transport chain, are upregulated during copper stress conditions (Chillappagari et al, 2010). It is likely that excess copper ions can cause ineffective electron transport, resulting in increased generation of superoxide anions.…”
Section: Characterization Of Ros Generated Upon Cucl 2 Exposurementioning
confidence: 99%
“…A recent finding has shown that iron-sulfur clusters are primary targets for copper toxicity (Chillappagari et al, 2010;Macomber & Imlay, 2009). Increased intracellular Cu(I) ions destabilize ironsulfur clusters, leading to functionally inactive proteins.…”
Section: Characterization Of Ros Generated Upon Cucl 2 Exposurementioning
confidence: 99%